An experimental and theoretical study of sandwich panels with TRC facings: Use of metallic connectors and TRC stiffeners. (15th April 2016) - Junes, A.; Si Larbi, A.
Highlights: Analysis of the behaviour of TRC facings sandwich panel. Identification of damage and failure mechanisms in the interaction between local (material) and global (structure) levels. Assessment of discrete connectors and stiffeners designed to improve the mechanical properties of the panels. Development of a simple calculation model designed to pre-dimensioning. Abstract: TRC composite material, made from a combination of fine-grained cement matrix and textile reinforcement, possesses properties, particularly mechanical ones, which makes it a suitable candidate a priori for the manufacture of low-thickness facings in applications such as sandwich panels. The aim of this study is to supplement and enrich as far as possible the rare studies dedicated to the subject. The aim, more precisely, is to add to the experimental database but also to attempt to make a useful contribution regarding damage and failure mechanisms as observed in the interplay between local and global levels. In addition, the possible use of discrete connectors and stiffeners designed to improve the mechanical properties of the panels is envisaged from a technological viewpoint and the consequences of the technological processes involved are assessed. Finally, a simple calculation model designed to help engineers with pre-dimensioning will be proposed and validated and its limits will be determined on the basis of a comparative theoretical/experimental study.